EFFECTS OF DIETARY BETA-GLUCAN ON GROWTH AND BODY COMPOSITION OF MACROBRACHIUM ROSENBERGII - S. J. MESHRAM; MURTHY, H. SHIVANANDA; H. S. SWAIN; H. ALI; T. D. JAGADEESH; H. B. DHAMGAYE (The Bioscan, 2014)
The experiment was carried out on Freshwater prawn, Macrobrachium rosenbergii, reared for a period of 60 days with a dietary supplementation of beta-glucan to evaluate the effect on growth, body composition and water quality changes. Juvenile of Macrobrachium rosenbergii (with initial weight of 0.34 ± 0.01 g) were fed with betaglucan incorporated diets at levels 0, 1, 2 and 3 g/kg of feed. The final weight of the prawn at the end of the experiment were 1.22g, 1.31g, 1.19 g and 1.13g fed with beta-glucan incorporated diets at levels 0, 1, 2 and 3 g/kg of feed respectively. There was no significant difference observed (p>0.05) in growth of experimental groups, however significant (p<0.05) survival rate (84%) was observed in prawn fed with 1 g/kg beta-glucan incorporated diet as compared to other treatments. Proximate composition showed no significant difference (p>0.05) among groups. Water quality parameters observed within the tolerance limits for M. rosenbergii during the experimental period. These results reveals that supplementation of dietary β-glucan 1g/kg could improve survival rate without affecting body composition in M. rosenbergii juvenile culture.